2021
DOI: 10.1016/j.celrep.2021.108743
|View full text |Cite
|
Sign up to set email alerts
|

TRIM67 regulates exocytic mode and neuronal morphogenesis via SNAP47

Abstract: Highlights d Unsupervised classifiers identify four exocytic classes in developing neurons d FVFi and FVFd modes insert membrane material; KNRi and KNRd do not insert membrane d TRIM67 limits SNAP47 SNARE complexes, promoting FVFi and membrane expansion d SNAP47 incorporation into SNARE complexes delays fusion pore expansion or closure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 81 publications
(143 reference statements)
1
15
0
Order By: Relevance
“…SNARE-mediated fusion is an essential mechanism that drives the synaptic transmission, neuron development, and growth. SNAP47 plays a role in exocytic mode and neuronal morphogenesis ( Holt et al., 2006 ; Urbina et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…SNARE-mediated fusion is an essential mechanism that drives the synaptic transmission, neuron development, and growth. SNAP47 plays a role in exocytic mode and neuronal morphogenesis ( Holt et al., 2006 ; Urbina et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicate that TRIM67 acts as an oncogene through the activation of Rho GTPase signaling-dependent membrane blebbing mechanism, leading to cell motility and tumor progression. Our findings illustrate a crucial oncogenic role of TRIM67 in gliomas apart from its essential biological roles in neural development, axon guidance, filopodia dynamics, exocytosis and synaptic vesicle formation (4,(6)(7)(8) In this context, our findings bring a novel player into the glioma biology, which appears to have essential consequences for oligodendroglioma progression. TRIM67 has been shown to have a dichotomous role in different cancers.…”
Section: Discussionmentioning
confidence: 65%
“…Next, we tested the interaction of TRIM67 with TRIM9, the TRIM family member with the closest sequence homology to TRIM67. Both proteins were previously found to associate with cytoskeleton (8), regulate filopodia extensions (6) and play essential roles in axon branching and synaptic vesicle formation (7). By western blotting, we detected a substantial increase in TRIM9 protein levels in three different cell lines (Supplemental Fig.…”
Section: Ectopic Trim67 Expression Induces the Formation Of Membrane Blebsmentioning
confidence: 60%
See 1 more Smart Citation
“…Currently, minimal information is known about TRIM67, although it is recognized to be capable of negatively regulating Ras activities by targeting 80K-H for degradation and then triggering neuritogenesis (24). In recent studies, TRIM67 has been reported that it's playing an important role in cancer development (25)(26)(27)(28) and brain development (29)(30)(31)(32). In this study, we performed a microscopic observation to investigate the effects of 22 TRIM proteins on the TNFa-induced nuclear translocation of p65.…”
Section: Introductionmentioning
confidence: 99%